Gut-ovary axis in polycystic ovary syndrome: mechanistic insights and gut microbiota-targeted therapeutic strategies - Zhao, Mei; Chen, Danlin; Hu, Xiumei; Xie, Caiping; Xu, Lianwei; Zhou, Fuhua (Frontiers in Endocrinology, 2025)
Polycystic ovary syndrome (PCOS) is a common endocrine and metabolic disorder that significantly affects women’s reproductive health and quality of life. Its pathogenesis involves multiple factors, including genetics, environment, and metabolism. In recent years, with the growing body of research on PCOS, the “gut-ovary axis” hypothesis has become a prominent research focus. This hypothesis suggests that an imbalance in gut bacteria may significantly influence the onset and progression of PCOS through various pathways, such as immune regulation, metabolic disturbances, and hormonal imbalances. This article aims to review the role of the “gut-ovary axis” in PCOS and to explore novel treatment strategies based on gut microbiota modulation, including probiotics, fecal microbiota transplantation, and dietary interventions. These strategies represent promising research avenues for future PCOS treatments, with preliminary studies demonstrating their potential to improve clinical symptoms. However, it is crucial to note that these are not yet established therapies and require substantial further validation. Novelty and Significance of this Review: This review moves beyond a descriptive catalog of associations to provide a critical appraisal of the gut-ovary axis in PCOS. We systematically differentiate well-established mechanisms from speculative hypotheses, explicitly identify persistent knowledge gaps, and evaluate the translational potential of microbiota-targeted therapies, thereby offering a refined framework for future basic and clinical research.